The Effect of Job Satisfaction, Organizational Communication and Organizational Commitment on Organizational Citizenship Behavior (Study at PT. Selamanya Sukses Abadi) - Herminingsih, Anik; Wartikah, Wartikah (Eduvest - Journal of Universal Studies, 2025)
This study aims to investigate the effect of job satisfaction, organizational communication, and organizational commitment on organizational citizenship behavior (OCB) at PT. Selamanya Sukses Abadi. Using a saturated sampling method, the study collects data from 50 employees through a survey questionnaire with a Likert scale. The analysis is conducted using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) method via Smart-PLS. The findings reveal that job satisfaction, organizational communication, and organizational commitment all have a positive and significant effect on OCB, indicating that improving these factors can enhance employee behavior that goes beyond job requirements. Specifically, job satisfaction had the strongest positive impact on OCB, followed by organizational communication and organizational commitment. The implications of this research are crucial for organizations aiming to improve OCB through strategies focused on increasing job satisfaction, improving communication, and fostering higher commitment among employees. For future research, it is recommended to explore the role of leadership styles and organizational culture as additional factors influencing OCB, as well as conducting longitudinal studies to examine the long-term effects of these variables on employee behavior and organizational performance.